Dynamic Evolution and Influencing Factor Modeling of Policy Instrument Selection for China’s Leisure Sports Industry - Bowen Zhang; Tianqi Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
China has transitioned to a "new normal" economy and reached the critical phase of constructing a moderately prosperous society on all fronts. Chinese individuals actively pursue a healthy lifestyle due to their rising living levels. National fitness, an essential tool for achieving universal health, has been raised to the status of a national policy. According to the connotation of the leisure industry and the characteristics of sports, the leisure sports industry can be characterized as a group of organizations that supply goods, services, and facilities to satisfy the consumption demands of individuals in the leisure sports sector. In a sense, the leisure sports sector can also be viewed as an industry that caters to people's leisure sports requirements. Against this backdrop, the growth of the leisure sports industry is destined to improve the health of everybody and generate a new economic growth sector. Sports industry policy instruments have the roles of communicating the vision of local government policy planning, promoting the achievement of policy goals, and resolving specific sports industry issues. This paper examines China's policy instruments for the leisure sports industry in recent years. It analyzes the factors influencing the selection of policy instruments for the leisure sports industry using multiple approaches, including a literature review, a comparative analysis, and a logic analysis. Several factors were recognized as impactors of policy instrument selection for the leisure sports industry, including policy objective, environment, instrument performance, and organizational path.